PROMOTING SELF-EFFICACY OF PROSPECTIVE MUSIC TEACHERS: THEORETICAL INSIGHTS - Bi, Guanhua (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Scientific literature shows that cultivating self-efficacy is conducive to learner in-depth study of music, independent choices and perseverance in the field of music. However, most current research studies focus on self-efficacy in primary and secondary education, whereas the self-efficacy of prospective music teachers has been scarcely investigated. Considering the importance of self-efficacy in music activities of prospective music teachers, a study on the particularity of prospective music teachers’ self-efficacy has been initiated: the literature analysis method has been used, and a large number of literature sources related to self-efficacy and music education have been analysed. The following problem question is formulated: what is the particularity of self-efficacy in music education? The aim of this research is to analyse the concept of self-efficacy in music education. Research results show that self-efficacy determines the judgment of prospective music teachers on their learning, performance, and teaching abilities. Factors that affect the self-efficacy of prospective music teachers include mastery of experiences, vicarious experience, social persuasion, and emotional and psychological states.